2016
DOI: 10.1097/shk.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Microparticles, Blood Cells, and Endothelium Induce Procoagulant Activity in Sepsis Through Phosphatidylserine Exposure

Abstract: Sepsis is invariably accompanied by altered coagulation cascade; however, the precise role of phosphatidylserine (PS) in inflammation-associated coagulopathy in sepsis has not been well elucidated. We explored the possibility of exposed PS on microparticles (MPs), blood cells, as well as on endothelium, and defined its role in procoagulant activity (PCA) in sepsis. PS-positive MPs and cells were detected by flow cytometry, while PCA was assessed with clotting time, purified coagulation complex, and fibrin form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 25 publications
7
79
0
2
Order By: Relevance
“…Several studies in vitro have confirmed that EMPs could mediate endothelial dysfunction, such as decline of angiopoiesis, vasorelaxation, nitric oxide production, proliferation and migration [8, 18, 26]. In our study, a pure population of bubble-induced EMPs was used and endothelial activity and function were injured after co-incubation with them.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies in vitro have confirmed that EMPs could mediate endothelial dysfunction, such as decline of angiopoiesis, vasorelaxation, nitric oxide production, proliferation and migration [8, 18, 26]. In our study, a pure population of bubble-induced EMPs was used and endothelial activity and function were injured after co-incubation with them.…”
Section: Discussionmentioning
confidence: 72%
“…79–81 Endothelial cell activation transforms the normally anticoagulant endothelial surface to a procoagulant phenotype. 82 Activated endothelial cells demonstrate increased expression of adhesion molecules (E-selectin, VCAM-1, ICAM-1), 74, 83, 84 von Willebrand Factor 85 , tissue factor (TF), 86 and proinflammatory cytokines, 87 decreased levels of endothelial cell-derived nitric oxide 88 and release microparticles with pro-inflammatory and procoagulant properties 89 , 90, 91 Monocyte activation may also be of importance in the pathogenesis of APS. Early studies demonstrated that anti-ÎČ2GPI antibodies activate monocytes in an annexin A2-dependent manner through a pathway involving Toll-like receptor 4 (TLR4) in lipid rafts.…”
Section: Pathogenesis Of Apsmentioning
confidence: 99%
“…MPs harboring endothelial-associated molecules were identified both in vitro and in vivo and therefore, were called endothelial MPs (EMPs) [7]. Increasing evidence suggests that EMPs not only constitute an emerging marker of endothelial injury, but can also be considered as important mediators capable of regulating a variety of biological functions, including inflammation, coagulation, angiogenesis and thrombosis [8, 9]. Thus EMPs appear to serve as both markers and hazards in vascular pathology [10-14].…”
Section: Introductionmentioning
confidence: 99%